Climate and land-use change during the late Holocene at Lake Ledro (southern Alps, Italy). (HoloceneHolocene, 2014)
This paper investigates the relative influences of climatic and anthropogenic factors in explaining environmental and societal changes in the southern Alps, Italy. We investigate a deep sediment core (LL081) from Lake Ledro (652 m a.s.l.). Environmental changes are reconstructed through multiproxy analysis, that is, pollen-based vegetation and climate reconstruction, magnetic susceptibility (MS), lake level, and flood frequency, and the paper focuses on the climate and land-use changes which occurred during the late Holocene. For this time interval, Lake Ledro records high mean water table, increasing amount of pollen-based precipitation, and more erosive conditions. Therefore, while a more humid late Holocene in the southern Alps has the potential to reinforce the forest presence, pollen evidence suggests that anthropogenic activities changed the impact of this regional scenario. Land-use activity (forest clearance for pastoralism, farming, and arboriculture) opened up the large vegetated slopes in the catchment of Lake Ledro, which in turn magnified the erosion related to the change in the precipitation pattern. The record of an almost continuous human occupation for the last 4100 cal. BP is divided into several land-use phases. On the one hand, forest redevelopments on abandoned or less cultivated areas appear to be climatically induced as they occurred in relation with well-known events such as the 2.8-kyr cold event and the ‘Little Ice Age’. On the other hand, climatically independent changes in land use or habitat modes are observed, such as the late-Bronze-Age lake-dwellings abandonment, the human population migration at c. 1600 cal. BP, and the period of the Black Death and famines at 600 cal. BP. [ABSTRACT FROM PUBLISHER]

Vegetation response to obliquity and precession forcing during the Mid-Pleistocene Transition in Western Mediterranean region (ODP site 976) (Quaternary Science Reviews, 2011)
The ODP leg 161 Site 976 (Alboran Sea) is a deep-sea section sampled at a water depth of 1108 m in the Western Mediterranean Sea. Pollen analysis provides a vegetation and climate record of the Mid Pleistocene Transition (MPT), roughly one million years ago. The age-model tied to biostratigraphic events was revised by aligning the pollen climate index (PCI) to Mediterranean (KC01b) and global (LR04) oxygen isotope records. The studied time slice spans the interval w1.09 Ma (MIS 31) to w0.90 Ma (MIS 23). Across this interval, past phytogeography of nowadays extinct taxa, which were rare, allows a successful application of the modern analogues technique (MAT) to quantitative climate reconstructions for the MPT. Five, long-term, obliquity-related vegetation successions (O1 to O5), and eight short-term, precessionrelated vegetation successions (P1 to P8) are observed within the studied interval. These vegetation successions, regardless of their duration, show the same pattern: the progressive replacement of temperate trees by mountainous taxa, and then by herbs and steppe maxima. Precession-related successions correspond, therefore, to as dramatic vegetation changes as those driven by obliquity, including a ﬁnal steppe phase under deteriorated climate conditions. Wavelet analysis of the PCI record shows that the Western Mediterranean experienced a shift at 1.01 Ma from precession-dominated frequencies (1.05e1.01 Ma) to obliquity-dominated frequencies (1.01e0.9 Ma). There is, therefore, an apparent discrepancy between wavelet analysis results and vegetation dynamic analysis (which suggests that obliquity and precession are recorded throughout the entire studied interval). This discrepancy could result from the fact that the PCI record sums, somehow, similar vegetation changes (wet to dry) occurring at different periodicities. Such a complex vegetation dynamics is mathematically rendered through a single parameter (i.e. principal component), which does not successfully catch the subtle combinations of variability occurring at two close periodicities. Furthermore, the pollen-inferred Early Pleistocene vegetation dynamic (and climate) of the Western Mediterranean region does not show a decrease of the obliquity response relative to the precession response at the onset of the MPT